Elementos barrocos en la obra esperpéntica de Valle-Inclán : una cala quevedesca - Swansey, Bruce (Trinity College (Dublin, Ireland). Department of Hispanic Studies, 2005)
Critical writing on the work of Valle-Inclan has focused mostly on its relation to aesthetic tendencies of his time, with the intention of assessing it in the context of European art. By contrast, his interest in Baroque culture, specifically in respect of Francisco de Quevedo, has yet to be fully studied. A substantial number of scholars have acknowledged, although in fragmentary fashion, connections between the festive works of Quevedo and the esperpentos of Valle-Inclan. Opinion has been divided, however, between those who maintain that such connections are only superficial and those who believe, on the contrary, that the literary techniques which characterize the esperpentos are indebted to Quevedo. To examine the relationship between the two writers, I have analyzed their inscription in the domain of the grotesque, the hybrid nature of Valle-Inclan's work, and its roots in the Baroque. This study seeks to contribute towards filling a critical void, concentrating on certain techniques favoured by both writers. Some of the coincidences between them can be grouped as follows: the position of the author as demiurge; the use of types rather than characters; the appropriation of situations characteristic of short farces; the function of costume; the use of histrionics and stage directions as elements of narrative technique; the peculiar way in which both writers depict the body in motion, their common taste for fragmentation, humanization, allegory and the animation of inert objects, and the employment of a bestiary that contributes to the characterization of their personages.
Keywords: Hispanic Studies, Ph.D.; Ph.D. Trinity College Dublin